University Education Role in Empowering Saudi Women in Light of Development Strategy 2030 from the Students' Perspective at Prince Sattam Bin Abdulaziz University - Dr. Alyaa Omar Ibrahim Farag; Dr. Wedad Abdullah Sharabi (مجلة الدراسات الاجتماعية, 2020)
This study aimed to identify the role of university education in empowering Saudi women in the light of the 2030 Development Strategy, and to identify the effect of some variables (study level, track, and university branch) on the role of University education from the perspective of female students. The descriptive method was used and a questionnaire, consisting of (47) items distributed over five dimensions, was designed for collecting data. A sample of (600) female students was randomly selected from Prince Sattam Bin Abdulaziz University. The study results revealed that University education has a role in achieving the 2030 Development Strategy regarding the social and economic empowerment of Saudi women. There were no differences in the participants' responses due to the variable of the study level. The results also showed that there were no differences in the students' perspective according to the track variable in all types of empowerment except for the institutional empowerment in favor of the Arts Track. The results also showed that there were no differences between the students' views according to branches variable in the branches (Al-Kharj, Al-Sulayyil and Wadi Al-Dawasir), while differences appeared in two branches (Al-Dalam and Al-Huta). The study stressed the importance of the role of university education in achieving the 2030 Development Strategy for empowering Saudi women, and raising students’ awareness about the importance of participation in developmental, cultural, economic and social activities.